The relationship of morphology, motor abilities and specific table tennis tasks of young table tennis players` and their competitive success - Nikolic, I.; Kondric, M.; Hublin, T. (Science and Racket Sports VI, 2019)
The aim of this research was to determine the influence of morphological characteristics, motor abilities and specific table tennis tasks on competitive success of young male Croatian table tennis players (N=60; aged 10-12 years, training experience 2.9±1.02 years). The participants were measured with 15 anthropometric measures, 24 motor tests and 6 specific table tennis tasks. After two years of measurements the competitive success was verified on points won and registered on the Croatian Table Tennis Association ranking lists for category (cadets and young cadets). Three separately regression analysis were applied and indicators of the relationships indicated that: in morphological variables the explained variance was 32%, in motor abilities variables 46%; while in table tennis variables the explained variance was 29%. The following variables have a positive influence on the criterion variable competitive success: arm length, shoulder biacromial breadth, beep test, hand plate tapping, side to side agility, knee push ups, shooting target on the ground using a racquet, dribbling the ball using a racquet. The obtained results should be useful to trainers, providing useful information for talent identification, as well as understanding important factors for a competitive success.